Investigating the Effect of Using Activity Based Costing (ABC) on Captive Product Pricing System in Internet Supply Chain Services - Ghaith Hakim Malik; Khalid Hasan Al jasimee; Gnan Abed kachi alhasan (International Journal of Supply Chain Management, 2019)
In this research, the impact of activity-based costing on captive product pricing strategies has been investigated. For a thorough examination, the important indicators of the impact of activity-based costing, which have been mentioned in most studies, have been used and also some examples of research have been reviewed to achieve the ultimate goal of the research. With regard to the use of activity based costing (ABC), and also taking into account the notion of compulsory pricing strategy, it can be concluded that secondary services in Internet supply chain services companies, despite the compulsion or dependence of the customer on secondary services and paying its fixed price, these pricing services are in tight competition among Internet supply chain service providers, and activity-based costing can help in better pricing and lead to competitive pricing for secondary services.